2022
DOI: 10.1155/2022/2523066
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes and Functions in Pneumoconiosis

Abstract: Pneumoconiosis is one of the most common occupational diseases in the world, and specific treatment methods of pneumoconiosis are lacking at present, so it carries great social and economic burdens. Pneumoconiosis, coronavirus disease 2019, and idiopathic pulmonary fibrosis all have similar typical pathological changes—pulmonary fibrosis. Pulmonary fibrosis is a chronic lung disease characterized by excessive deposition of the extracellular matrix and remodeling of the lung tissue structure. Clarifying the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 112 publications
(202 reference statements)
0
4
0
Order By: Relevance
“…Epigenetic modifications are processes that alter gene activity without modifying the underlying genetic code. An expanding body of evidence indicates that epigenetic changes play a significant role in IPF [120]. DNA methylation variations encompass unintentional methylation errors and the hyper-and hypomethylation of cytosine residues in various genes [121].…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…Epigenetic modifications are processes that alter gene activity without modifying the underlying genetic code. An expanding body of evidence indicates that epigenetic changes play a significant role in IPF [120]. DNA methylation variations encompass unintentional methylation errors and the hyper-and hypomethylation of cytosine residues in various genes [121].…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…Nevertheless, growing evidence suggests that passenger strand can also be biologically active, and miRNAs are furthermore capable of interacting with proteins and DNAs, not only restricted to mRNAs [ 16 ]. Even more striking, contrary to the widely-accepted negative regulatory role, studies have found that nuclear activating miRNAs (NamiRNAs) could positively regulate gene expressions by enhancing the enhancer activation or competitively binding repressor proteins [ 17 , 18 ]. Clearly, more work is required to fully illuminate the regulatory role of miRNAs involved in various biological processes.…”
Section: Background Of Mirnasmentioning
confidence: 99%
“…100 pneumoconiosis patients hospitalized in our hospital from December 2022 to January 2023 were selected as the research subjects, including 67 male patients and 13 female patients; The average age is (53.24 ± 9.18) years old; Initial diagnosis period: 77 cases in the first stage, 16 cases in the second stage, and 7 cases in the third stage; Inclusion criteria: All patients met the diagnostic criteria of "Diagnosis of Occupational Pneumoconiosis" [5] (GBZ 70-2015). (1) All patients were diagnosed as chronic pneumoconiosis patients through imaging, pathology, surgery, and other examinations; (2) No other serious illness patients; (3) The patient is aware of the purpose and content of this study and agrees to cooperate and sign a letter of understanding; (4) This study was approved by the hospital ethics committee. Exclusion criteria: (1) Patients with severe functional failure such as heart, liver, and kidney; (2) Failure to complete relevant inspections; (3) Those who are unwilling to cooperate during follow-up.…”
Section: Research Subjectsmentioning
confidence: 99%
“…It is a systemic disease. According to current occupational epidemiology, there are over 20 million township enterprises in China with over 200 million employees, of which 16% are engaged in dust exposure operations [1][2] . Due to the backwardness of the enterprise industry and the fact that the employees are mainly farmers, there is a lack of knowledge about the hazards of dust, and there are no guarantee measures in work.…”
Section: Introductionmentioning
confidence: 99%